Turcos, moros e indios bárbaros: Globalización y diplomacia transcultural en el imperio hispano de Carlos III - Pablo Hernández Sau (Mélanges de la Casa de Velázquez)
During the last third of the eighteenth century Spanish ministers showed a growing interest in establishing permanent peaceful relations with Muslim states in the Maghreb and the eastern Mediterranean, such as the Ottoman and Alawite empires; as well as with all kinds of Amerindian peoples in the Mississippi Valley, such as the Creeks, Talapuches or Tunicas. How can we explain this coincidence? How can we analyse this growing Hispanic interest in Turks, Moors, and barbarian Indians? Based on the use of global microhistory, this article argues for the need to analyse jointly Hispanic diplomacy and diplomatic practices vis-à-vis non-Christian and independent states in various parts of the Mediterranean and the enlightened Atlantic, seeking to understand the implications of globalisation for Hispanic imperial policy and its growing weight for the Bourbons. In line with this, the article explains the active Carolinian representation and convergences in the practices of transcultural diplomacy, highlighting the global interdependence between regional conflicts in the development of the Hispanic policy of Charles III.